Neuroendocrine abnormalities in a neonate with congenital toxoplasmosis. - Tania Siahanidou; Tsoumas, Dimitris; Kanaka-Gantenbein, Christina; Mandyla, Helen (J Pediatr Endocrinol Metab, 2006)
The central nervous system is often affected in patients with congenital toxoplasmosis. However, hypothalamo-pituitary dysfunction has rarely been reported in children with congenital toxoplasmosis, and no case with prolonged fever of central origin has been documented so far. We describe a newborn with congenital toxoplasmosis who presented with fever due to hypothalamo-pituitary dysregulation and combined hypothalamo-pituitary deficiencies consisting of central diabetes insipidus, hypothyroidism and ACTH deficiency.
Keywords: Adrenocorticotropic Hormone; Congenital; Congenital Hypothyroidism; Diabetes Insipidus; Fever; Humans; Hypothalamo-Hypophyseal System; Infant; Male; Neurogenic; Newborn; Toxoplasmosis